Near‐infrared bulk optical properties of goat wound tissue and human serum: consequences for an implantable optical glucose sensor. Issue 10 (8th December 2015) - Aernouts, Ben; Sharma, Sandeep; Gellynck, Karolien; Vlaminck, Lieven; Cornelissen, Maria; Saeys, Wouter
Abstract : Near‐infrared (NIR) spectroscopy offers a promising technological platform for continuous glucose monitoring in the human body. Moreover, these measurements could be performed in vivo with an implantable single‐chip based optical sensor. However, a thin tissue layer may grow in the optical path of the sensor. As most biological tissues are highly scattering, they only allow a small fraction of the collimated light to pass, significantly reducing the light throughput. To quantify the effect of a thin tissue layer in the optical path, the bulk optical properties of serum and tissue samples grown on implanted dummy sensors were characterized using double integrating sphere and unscattered transmittance measurements. The estimated bulk optical properties were then used to calculate the light attenuation through a thin tissue layer. The combination band of glucose was found to be the better option, relative to the first overtone band, as the absorptivity of glucose molecules is higher, while the reduction in unscattered transmittance due to tissue growth is less. Additionally, as the wound tissue was found to be highly scattering, the unscattered transmittance of the tissue layer is expected to be very low. Therefore, a sensor configuration which measures the diffuse transmittance and/or reflectance instead was recommended.(a ) Dummy sensor; (b ) explanted dummy sensor in tissue lump; (c ) removal of dummy sensor from tissue lump; and (d ) 900 µm slices of tissue lump. Abstract : In vivo glucose monitoring with an implantable sensor would significantly facilitate life for people with diabetes. NIR technology combines the properties which would allow for accurate estimation of the analyte concentration. However, a thin layer of wound tissue may grow in the optical path of the sensor, seriously reducing the light throughput. In this study, the bulk optical properties of wound tissue and serum are measured, compared and discussed with respect to the optimal design of an implantable NIR glucose sensor.